Nutrient‐charged biochars increased nutrient‐use efficiency in a cotton–maize rotation in Burkina Faso. (13th March 2023) - Saba, Fatimata; Cornelis, Jean‐Thomas; Sawadogo, Hamado; Lefebvre, David; Bacia, Rabiatou K. I.; Cisse, Drissa; Bandaogo, Alimata A.; Mamadou, Traore; Nacro, Hassan‐Bismarck
Abstract: Soil nutrient depletion, low crop nutrient‐use efficiency, and limited access to fertilizers are serious issues leading to poor yield in agroecosystems of Burkina Faso. Blending biochars with organic or inorganic nutrients could slow down nutrient release, which can enhance fertilizer‐use efficiency. This study investigates whether charging biochar with nutrients and Acacia gum ( Acacia senegal L.) coating can improve nutrient‐use efficiency in a cotton ( Gossypium hirsutum L.)–maize ( Zea mays L.) rotation system using low application rates (<5 t ha −1 ). The experiment was conducted in western Burkina Faso during three cropping seasons (2018–2020) with five treatments: T0, control; T1, conventional practice with compost and nitrogen (N), phosphorus (P), and potassium (K) application; T2, microdose (planting hole application) of NPK; T3. nutrient‐charged biochar activated with dissolved NPK; T4, nutrient‐charged biochar activated with dissolved NPK and coated with Acacia gum. Biochar‐based fertilizers significantly increased soil organic C content, as well as bioavailable P and calcium (Ca), without significantly improving crop yields, compared to conventional practice and microdose of NPK. When nutrient‐charged biochar was coated with Acacia gum, N‐use efficiency (NUE; N recovered in grain/N fertilized) was improved compared to uncoated nutrient‐charged biochar, although the difference was not significant. Despite no significant effects on crop yields during three cropping seasons, the use of coated biochar‐based fertilizer may be a technically effective solution to improve NUE in the long term in agroecosystems characterized by nutrient‐impoverished soils under a constraining South‐Sudanese climate. Core Ideas: Biochar‐based fertilizers increased maize grain yields by 16% compared to microdose NPK application. Using conventional or biochar microdosing improved N‐use efficiency relative to broadcast fertilizer application. Coating biochar with Acacia gum increased the nutrient‐use efficiency of the nutrient‐charged biochar.